Pengaruh Brand Image dan Brand Awareness terhadap Keputusan Pembelian Body Lotion Vaseline (Studi pada Pengguna Body Lotion Vaseline di TikTok Shop) - Munawaroh, Ana; Herlina, Listri (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to describe purchasing decisions, brand image, and brand awareness and analyze the influence of brand image and brand awareness on the purchasing decisions of Vaseline body lotion users at the TikTok Shop. The research uses quantitative methods with descriptive and verification approaches. Samples were taken through purposive sampling involving 100 Vaseline body lotion users at the TikTok Shop, and data was collected through a questionnaire. Data analysis includes multiple linear regression, correlation coefficient, and coefficient of determination. Descriptive analysis shows a purchasing decision score of 3,353 (very good), brand image 2,445 (good), and brand awareness 2,678 (very good). The research results show that brand image influences purchasing decisions with a correlation of 0.825 and brand awareness with a correlation of 0.813. Simultaneously, brand image and brand awareness influence purchasing decision with a simultaneous correlation of 0.935 and an influence contribution of 87.4%.